2018
DOI: 10.1088/1361-6528/aadad8
|View full text |Cite
|
Sign up to set email alerts
|

p-GaN/n-ZnO nanorods: the use of graphene nanosheets composites to increase charge separation in self-powered visible-blind UV photodetectors

Abstract: ZnO-based heterojunctions have found applications as self-powered ultraviolet photodetectors (PDs). However, high doping levels are not compatible with high mobility for metallic doped ZnO-based PDs so further development has been inhibited. This study demonstrates a method to increase the open-circuit voltage (V ) that allows keeping a sufficiently high level of mobility of ZnO, using a ZnO nanorod/GaN heterojunction that incorporates graphene nanosheets as the active layer. These hybrid PDs have triple the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Ultraviolet (UV) photodetectors (PDs) are widely used for biological analysis, flame monitoring, environmental sensing, and space exploration. To reduce or eliminate energy consumption, many studies propose self-powered UV PDs that convert incident UV light into an electrical signal, so there is no need for an external power supply. , UV PDs that operate at zero bias usually have a p–n heterojunction structure because the built-in electrical field prevents the recombination of photogenerated electron–hole pairs. However, the vertical structure of a p–n photodiode that has two different electrodes on opposite sides is complex, and the large lattice mismatch at the interfaces in the heterostructure result in a significant reduction in the performance of the device. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet (UV) photodetectors (PDs) are widely used for biological analysis, flame monitoring, environmental sensing, and space exploration. To reduce or eliminate energy consumption, many studies propose self-powered UV PDs that convert incident UV light into an electrical signal, so there is no need for an external power supply. , UV PDs that operate at zero bias usually have a p–n heterojunction structure because the built-in electrical field prevents the recombination of photogenerated electron–hole pairs. However, the vertical structure of a p–n photodiode that has two different electrodes on opposite sides is complex, and the large lattice mismatch at the interfaces in the heterostructure result in a significant reduction in the performance of the device. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [37], fabricated a photodetector based on zinc oxide quantum dots and CDs, which achieved a detectivity and noise equivalent power of 3.1 × 10 17 cmHz 1/2 /W and 7.8 × 10 −20 W, respectively. Moreover, in photosensing applications, it has been demonstrated that the photoresponsivity of p-n junction based photodetectors can be increased by the use of graphene nanosheets composites [38,39]. Dai et al [40], demonstrated transparent and flexible (TFT) based on solution processed-graphene nanosheets and amorphous indium-gallium-zinc-oxide (a-IGZO) composites, with an achieved mobility of 23.8 (cm 2 V −1 s −1 ), which is about thirty times higher than that of the pristine a-IGZO TFTs (0.82 cm 2 V −1 s −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, Zhu and co-workers reported a ZnO film/p-GaN heterojunction self-powered UV PD with a [12]. In order to enhance the response performance of the self-powered UV PDs, many different materials such as CdS, MgO, graphene, CsPbBr 3 , have been used to couple with ZnO/p-GaN heterojunction [13][14][15][16][17]. Copper oxide (CuO), as a typical transition-metal oxide semiconductor, has drawn extensive attention in the research fields of photoelectric detectors [18].…”
Section: Introductionmentioning
confidence: 99%